Dinâmica de emaranhamento de dois átomos no modelo de Jaynes-Cummings-Hubbard - Broni, Eugene Mawuli (2022)
The entanglement dynamics of the Jaynes-Cummings-Hubbard model is studied. With concurrence as the measure of entanglement, the model is explored for single and double excitation states, considering several initial states. For each initial state specified, the effect of the hopping strength is graphically observed for zero and non-zero detunings, and, symmetric and asymmetric atom-cavity coupling strengths as applicable. The cases for zero hopping reproduce results, for the double Jaynes-Cummings model, that are well documented in literature. For the single excitation cases, there are results of complete and incomplete transfer of atom-atom entanglement to bipartite subsystems and for a specified Bell state, depending on the detuning value. In the cases of the double excitation, there is a general suppression of Entanglement Sudden Death (ESD) and atomic entanglement with increase in the hopping strength, depending on the initial state.